Appropriations Of Places Of Fear And Memory: Perceptions Of Women From Comuna 1, Medellín, Colombia - Pineda Zapata, Maria Isabel (Universidad Pedagógica y Tecnológica de Colombia, 2018)
The present article describes how women of La Avanzada and Carpinelo, neighborhoods of Medellin, have appropriated places within them, that evoke fear and memory. The article answers the questions: ¿What are the places of fear and memory for women, what perceptions do they have and how do they appropriate them? The argumentation weaves the relationship between gender and territory from two approaches: culture and feminist geography. The methodological included tours of the places, elaboration of social cartographies and group and individual interviews. The results show how fear and insecurity that women feel in some places of their neighborhoods, have been creating boundaries that prevent its uses. These factors have limited the appropriation of those places by the community, restricting liberty and autonomy, crucial factors to the foundation of a city perceived safe for women.